Women and gambling-related harm: a narrative literature review and implications for research, policy, and practice - Simone McCarthy; Samantha L. Thomas; Maria E. Bellringer; Rebecca Cassidy (BMC, 2019)
Abstract Background While the prevalence of women's participation in gambling is steadily increasing, there is a well-recognised male bias in gambling research and policy. Few papers have sought to synthesise the literature relating to women and gambling-related harm and provide practical suggestions to guide future research, policy, and practice which take into account the specific nuances associated with women's gambling. Methods A narrative literature review was conducted to review the evidence base on women's gambling behaviours and experiences of harm. Drawing from strategies used effectively in other areas of public health, key elements for a gendered approach to harm prevention were identified and adapted into practical public health research, policy and practice strategies. Results Results indicated a lack of research that explores women's gambling. Few studies have examined the impact of gambling on the lives of women, with limited understanding of the factors that influence women's engagement with gambling products, and the impact of industry tactics. A gendered approach was identified as a strategy used successfully in other areas of public health to shift the focus onto women and to ensure they are considered in research. In tobacco control, increasing trends in women's smoking behaviour were combatted with targeted research, policy and practical initiatives. These key elements were adapted to create a conceptual framework for reducing and preventing gambling harm in women. The framework provides regulatory direction and a research agenda to minimise gambling-related harm for women both in Australia and internationally. Evidence-based policies should be implemented to focus on the influence of gender and associated factors to address gambling-related harm. Practical interventions must take into account how women conceptualise and respond to gambling risk in order to develop specific harm prevention programs which respond to their needs. Conclusion A gendered approach to gambling harm prevention shifts the focus onto the unique factors associated with women's gambling and specific ways to prevent harm. As seen in other areas of public health, such a framework enables harm measures, policies, and interventions to be developed that are salient to girls and women's lives, experiences and circumstances.